The Time Is Now: Bioethics and LGBT Issues - Powell, Tia (The Hastings Center report, 2014)
Our goal in producing this special issue is to encourage our colleagues to incorporate topics related to LGBT populations into bioethics curricula and scholarship. Bioethics has only rarely examined the ways in which law and medicine have defined, regulated, and often oppressed sexual minorities. This is an error on the part of bioethics. Medicine and law have served in the past as society's enforcement arm toward sexual minorities, in ways that robbed many people of their dignity. We feel that bioethics has an obligation to discuss that history and to help us as a society take responsibility for it. We can address only a small number of topics in this special issue of the Hastings Center Report, and we selected topics we believe will stimulate discourse. Andrew Solomon offers an elegant overview of the challenges that bioethics faces in articulating a solid basis for LGBT rights. Timothy F. Murphy asks whether bioethics still faces issues related to lesbian, gay, and bisexual people, given the deletion of homosexuality as a disease and the progress toward same-sex marriage. Jamie Lindemann Nelson's essay addresses the search for identity for transgender persons and the role of science in that search. Two articles, those by Brendan S. Abel and by Jack Drescher and Jack Pula, take up the complex issue of medical treatment for children who reject their assigned birth gender. Celia B. Fisher and Brian Mustanski address the special challenges of engaging LGBT youth in research, balancing the need for better information about this vulnerable group against the existing restrictions on research involving children. Tia Powell and Edward Stein consider the merits of legal bans on psychotherapies intended to change sexual orientation, particularly in the light of current research on orientation. Mary Beth Foglia and Karen I. Fredricksen-Goldsen highlight health disparities and resilience among LGBT older adults and then discuss the role of nonconscious bias in perpetuating disparities. Stephan Davis and Nancy Berlinger assess the challenges of access to care and health policy for transgender persons. Edward J. Callahan et al. tackle the ways in which diverse aspects of medicine should change to better incorporate the needs of LGBT patients, including through use of the electronic medical record, education of health professionals, and recruitment efforts for LGBT health professionals. Virginia Ashby Sharpe and Uchenna S. Uchendu describe multifaceted efforts within Veterans Administration facilities to create change for LGBT veterans across the largest integrated health care network in the United States. Lance Wahlert and Autumn Fiester find a mixed record in the use of case studies in teaching about LGBT issues